(3GdGWGQ GdfXQj h GdJWHjb GdYedjs - (3djK YHO Gddg(B, (3Gdbgjhjs; (3GdhGOj HdGd eMehO(B, s ((3YeGf(B:s (3OGQ GdMGeO(B,s, 2012)
(3ebOeI ddTQGcI Hjf GdbWGYjf GdYGe h GdNGU h JMdjd GdTQGcI h eQGMdgG , WdH GdTQGcI Hjf GdbWGYjf GdYGe h GdNGU h GdNWhGJ GddGReI dPdc , GdTQjc GdNGU , GOGQI YbhO GdTQGcI , GOGQI eTGQjY GdTQGcI Hjf GdbWGYjf HGdJWQb Gdi (B: (3GOGQI GdeNGWQ , GdSjGSGJ h GdbhGfjf GdLOjOI h GdeLOOI , GdGOGQI GdeGdjI , GdehGabGJ GdMchejI , GdGJUGd h GdGYdGe h eTGcd CUMGH GdeUdMI h GOGQI GdYdGbGJ , GOGQI GdehGQO GdHTQjI h aV GdfRGYGJ , GOGQI GdeYQaI Ydi eSJhi GdeTQhY h Ydi GdeSJhi GdhWfj , eQGLYI eTGQjY GdTQGcI Hjf gPjf GdbWGYjf , eaghe GdTQGcI Hjf GdbWGYjf GdYGe h GdNGU aj eLGd GdeSDhdjI GdGLJeGYjIs
(3agQS GdGTcGd U(B.13s
Keywords: (3GdTQGcIs; (3GdbWGY GdNGUs; (3GdbWGY GdYGes